An Advanced Encryption Standard Powered Mutual Authentication Protocol Based on Elliptic Curve Cryptography for RFID, Proven on WISP. (31st August 2017) - Ibrahim, Alaauldin; Dalkılıç, Gökhan
Abstract : Information in patients' medical histories is subject to various security and privacy concerns. Meanwhile, any modification or error in a patient's medical data may cause serious or even fatal harm. To protect and transfer this valuable and sensitive information in a secure manner, radio-frequency identification (RFID) technology has been widely adopted in healthcare systems and is being deployed in many hospitals. In this paper, we propose a mutual authentication protocol for RFID tags based on elliptic curve cryptography and advanced encryption standard. Unlike existing authentication protocols, which only send the tag ID securely, the proposed protocol could also send the valuable data stored in the tag in an encrypted pattern. The proposed protocol is not simply a theoretical construct; it has been coded and tested on an experimental RFID tag. The proposed scheme achieves mutual authentication in just two steps and satisfies all the essential security requirements of RFID-based healthcare systems.